Issues in Modern Pharmaceutical Packaging - An Indian Perspective: Issues in Modern Pharmaceutical Packaging - An Indian Perspective - Vinodhini, C. (International Journal of Pharmaceutical & Biological Archive, 2019)
Indian Pharmaceutical Industry predicting to develop USD 2.60 million by 2020. This contribution will be helpful in the growth of the Indian economy; on another hand, it will set up new challenge. The World Health Organization guideline defined packaging is a process that bulk material must undergo to become finished products. Packaging will not only protect the drug from degradation but also contamination; it will become an important part of drug delivery system. In this review, issues faced by packaging industry such as environmental pollution, regulatory requirements, patient compliances, and anticounterfeiting have described detail. Pharmaceutical packaging industry must involve in the research and development activity to find out the solutions for the issues to produce the product in quality, safety, and effective way to consume.